2007
DOI: 10.3354/meps338021
|View full text |Cite
|
Sign up to set email alerts
|

Functional and structural responses of marine plankton food web to pyrene contamination

Abstract: The effects of single additions of pyrene (low, medium or high) on a natural marine plankton community are reported in this study. Direct and indirect effects on the function and structure of bacteria, phytoplankton and zooplankton communities were investigated using a food-web approach in a mesocosm. Phytoplankton communities suffered from direct effects of the exposure to pyrene and, after a lag-period of 2 d, so did the bacterial communities exposed to medium and high pyrene concentrations. Effects on the z… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
22
2

Year Published

2008
2008
2024
2024

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 44 publications
(25 citation statements)
references
References 36 publications
1
22
2
Order By: Relevance
“…The mesocosm experiment was carried out in the Isefjord, Denmark (average depth 5 to 7 m), for 12 d in April and May 2005 in a similar manner as described in Hjorth et al (2007). Twelve mesocosm bags (3 m 3 ) were established, creating 3 replicate mesocosms per experimental treatment.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…The mesocosm experiment was carried out in the Isefjord, Denmark (average depth 5 to 7 m), for 12 d in April and May 2005 in a similar manner as described in Hjorth et al (2007). Twelve mesocosm bags (3 m 3 ) were established, creating 3 replicate mesocosms per experimental treatment.…”
Section: Methodsmentioning
confidence: 99%
“…The productivity can be bottom-up controlled, with abiotic conditions such as light, temperature and nutrients determining production rates, and where PAH exposure may affect primary producers more severely under these conditions. This was the case as determined by Hjorth et al (2007) who suggested phytoplankton are the most susceptible group, and declines in their biomass and/or activity lead to indirect effects in bacterial and zooplankton communities. On the other hand, a system can be top-down controlled where primary production is limited by predation from other trophic levels.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…These compounds are found in high concentrations in diesel fuel and other common hydrocarbon mixtures. Oil spills containing these compounds have been shown to drastically alter biodiversity in marine systems, ranging from large fish to planktonic communities (Incardona et al 2004, Hjorth et al 2007). …”
Section: Introductionmentioning
confidence: 99%